2009
DOI: 10.1111/j.1365-2109.2009.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of physiological filtration variables forCrassostrea corteziensis(Hertlein, 1951) andAnadara tuberculosa(Sowerby, 1833) in shrimp aquaculture effluents

Abstract: This study examined the main ¢ltration variables [¢ltration rate (FR), clearance rate (CR) and assimilation e⁄ciency (AE)] of the Cortez oyster, Crassostrea corteziensis (Hertlein, 1951), and the mud cockle, Anadara tuberculosa (Sowerby, 1833), in shrimp aquaculture e¥uents at three di¡erent £ux velocities (1.5, 3 and 4.5 L h À 1 ) using a 36-respirometer system, each with a 0.5 L capacity. Under inverted photoperiod conditions, free variations in the environmental parameters were allowed to mimic e¥uent condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…fresh algal diets and particle concentrations). Low CRs of 0.04–0.10 L g –1 h –1 ( Crassostrea corteziensis ) and 0.33–0.56 L g –1 h –1 ( Anaara tuberculosa ) were also observed for other bivalve mollusks depending on the experimental conditions [ 62 ]. Considering the previous finding that the CR of R .…”
Section: Discussionmentioning
confidence: 99%
“…fresh algal diets and particle concentrations). Low CRs of 0.04–0.10 L g –1 h –1 ( Crassostrea corteziensis ) and 0.33–0.56 L g –1 h –1 ( Anaara tuberculosa ) were also observed for other bivalve mollusks depending on the experimental conditions [ 62 ]. Considering the previous finding that the CR of R .…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that nutritional value of cultured microalgae, Skeletonema costatum, and shrimp effluent as food sources for the Pacific oyster, Crassostrea gigas, not finding significant differences between both sources Lefebvre et al, (2000). Several other commercially important bivalves, e.g., Anadara grandis, A. tuberculosa, Crassostrea corteziensi has been reported for having excellent bioremediation properties for the shrimp effluents (Miranda-Baeza et al, 2006, Wilber et al,2006, Peña-Messina et al, 2009. The high survival of clams after the trial, suggests that the shrimp pond effluent may be an acceptable environment for the growth of the species, especially at the lower density (12.5 /m 2 ) where a survival of 85% was observed by Martínez-Córdova et al, (2011).…”
Section: Diversification Via Synergy: Mussels As Bioremediation Agentmentioning
confidence: 82%
“…This last species is a native oyster with marketable value (Trabal‐Fernández et al, 2014), that is adapted to local environmental conditions such as high temperature and elevated precipitation seasons. The pleasure oyster is cultivated all year round (Castillo‐Durán et al, 2010) and has been suggested as a good candidate for bioremediation for shrimp farming effluents (Garza‐Aguirre et al, 2013; Peña‐Messina et al, 2009). Therefore, this species may be considered as a suitable candidate for evaluating growth performance using different zootechnical management strategies in relatively deep effluent drainage channels from shrimp farms.…”
Section: Introductionmentioning
confidence: 99%